Hubungan Antara Layanan Keperawatan Dengan Tingkat Kepuasan Pasien Di Klinik Pratama Badan Pusat Statistik: The Relationship Between Nursing Services and the Level of Patient Satisfaction at the Pratama Clinic Central Agency for Statistics - Prabawa, Satria (Dohara POAJ, 2025)
Introduction: A nursing service is said to be good if it fulfills patient needs according to standards, and good service will create a level of patient satisfaction according to standards. There are 5 factors that influence patient satisfaction, namely responsiveness, reliability, assurance, empathy and physical evidence. With these factors, patients can assess the nursing care they receive and can perceive whether it is in accordance with what the patient wants or not. Method: The data scale for this research is an ordinal scale and uses a scatter statistical test. Spearman Rho is one of the non-parametric associative bivariate tests. This means that a non-parametric test is used to see the strength of the relationship between two variables that have an ordinal measurement scale. Results: The research results showed that the Spearman statistical test results for the Nursing Service and Satisfaction variables had a degree of significance of p (0,001) which means that the statistical test results showed p < 0,05; so H1 was accepted and meant there was a relationship between the two variables. Judging from the results of the Correlation Coefficient or how strong the relationship between two variables with the result of 0,744 which means it is very strong. Discussion: There is a relationship between nursing services and the level of patient satisfaction at the Pratama Clinic of the Central Bureau of Statistics.